Low-energy ion beam modification of horticultural plants for induction of mutation - A. Krasaechai (2018)
Low-energy ion beam biotechnology, as a newly established and developed highly interdisciplinary technology, has been vigorously applied to modification of horticultural plants for induction of mutations at Chiang Mai University (CMU). Chiang Mai is the horticultural center of Thailand with a magnificent variety of floral resources thanks to its peculiarly favorable environment and climate. Ion beam bombardment induced mutations of flowers have further exploited the horticultural potential. This paper reports recent progress in research and applications of ion beam biotechnology for floral mutation at CMU. Ions at low energies of several tens of keV were implanted into flower seeds, buds and receptacles of various species in vacuum to fluences of an order of 1016 ions/cm2using self-developed special techniques for the living organism survival. A broad spectrum of mutants has been obtained including changes in phenotypes such as the flower color, color intensity, flower shape, and petal shape and size. DNA-fingerprint analysis revealed changes at the DNA level. Physical mechanisms involved in the ion beam induction have been investigated, and however still remained obscure. © 2009 Elsevier B.V. All rights reserved.